Analisis Situasi Komunikatif Komunitas Bright Up Indonesia dimasa Pandemi Covid-19 - Fernindy Intan Putri; Zainal Abidin; Ana Fitriana Poerana (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2021)
AbstractThe Covid-19 pandemic has affected various aspects of human life, ranging from aspects of education, social, economy, tourism, and even the way humans communicate. During the Covid-19 pandemic, direct (face to face) communication is now no longer a main priority. The Bright Up Indonesia Community is a non-profit social community has also felt the impact of change in communication culture during the Covid-19 pandemic. Where in current crisis, the Bright Up Indonesian community must be able to survive, adapt to technology, be creative and innovative in order to continue carrying out activities in accordance with organizational goals. The purpose of this research is to find out how “The communication event of Bright Up Indonesia Community during the Covid-19 Pandemic”. This research uses a qualitative research method with a virtual ethnographic approach. The result of this research indicates a change in communication culture of community during the Covid-19 pandemic.Keywords: Communication Cultures, Community, Pandemic Covid-19, CMCAbstraksiPandemi Covid-19 terbukti telah mempengaruhi berbagai aspek kehidupan manusia, mulai dari aspek pendidikan, sosial, ekonomi, pariwisata, bahkan cara manusia berkomunikasi. Bright Up Indonesia merupakan sebuah komunitas sosial bersifat non profit yang ikut merasakan dampak dari perubahan budaya komunikasi dimasa pandemi covid-19 ini. Dimana dalam kondisi krisis seperti saat ini komunitas Bright Up Indonesia harus bisa tetap survive, beradaptasi dengan teknologi , kreatif dan inovatif untuk tetap bisa menjalankan kegiatan sesuai dengan tujuan organisasinya. Tujuan dari penelitian ini adalah untuk mengetahui Bagaimana “Analisis Aktivitas Komunikasi Komunitas Bright Up Indonesia Dimasa Pandemi Covid-19”. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan etnografi virtual. Hasil dari penelitian ini menunjukkan adanya perubahan budaya komunikasi komunitas dimasa pandemi Covid-19.Kata Kunci: Budaya Komunikasi, Komunitas, Pandemi Covid-19, CM